Does expatriate production prejudice exports? - Gerd Tacke (Intereconomics, 1967)
Increasingly, German firms are adopting the practice of setting up production units abroad. The public is not altogether in favour of this trend. It is argued that in so doing German industry is creating a stick for its own back and may possibly—in the long term— prejudice its own export opportunities. In an attempt to clarify these complex questions INTERECONOMICS has talked with Dr Tacke, a member of the Board of SIEMENS AG., who has for many years been responsible for SIEMENS' foreign policy.
Keywords: 330; Interview